Factors Influencing the Hygiene Behavior of Food Handlers in Cikarang Bekasi Catering Services - Helmi; Endarti, Ajeng Tias; Prahastuti, Brian Sri (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Law of the Republic of Indonesia Number 18 of 2012 concerning Food mandates the preparation of safe food consumption that can be done with hygiene. One party that can play a role in ensuring safe food consumption is the Catering Service provider. Unfortunately, most catering entrepreneurs in Indonesia do not understand the hygiene requirements that are closely related to health. Hygiene behavior in food handlers greatly affects the quality of catering food. From the researcher's initial survey, there were several catering services that had poor hygiene behavior. This study aims to determine the factors that influence the hygiene behavior of food handlers in the Cikarang catering service, Bekasi Regency in 2024. This study is a quantitative cross-sectional design study. The sample of this study was 100 food handlers in the Cikarang Bekasi catering service. Data collection was carried out by interview using a questionnaire. The analysis of this study was univariate, bivariate and multivariate. The univariate results showed that most respondents had poor food handler hygiene behavior (65.0%). Bivariate results showed a relationship between education, knowledge, attitude, PPE, facilities and infrastructure, superior support, friend support, counseling with food handler hygiene behavior (P <0.05). Multivariate results showed that the PPE variable was the dominant variable that influenced food handler hygiene behavior with OR 174 (95%CI 21-1432). Conduct routine socialization and counseling of food handler hygiene. Counseling can be carried out by the health center.